2020
DOI: 10.1021/acs.iecr.9b06617
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Idealized Models of Nanoscale Metal Hydrides for Hydrogen Storage

Abstract: Metal hydrides are attractive for compact, lowpressure hydrogen storage, yet a foundational understanding of factors governing their thermodynamics and kinetics is still lacking. Predictive modeling from the atomic to the microstructural scale plays a critical role in addressing these gaps, particularly for nanoscale materials, which promise improved performance but are difficult to probe. Here, we summarize strategies being developed within the Hydrogen MaterialsAdvanced Research Consortium (HyMARC) for goin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Under hydrogenation conditions, it is reasonable to assume that such sites could function as the predominant “scissors” for H 2 cleavage. As exothermic atomic H diffusion is expected to be facile, exemplified by low H diffusion barriers 35 in bulk MgB 2 and on the pristine Mg-terminated (0001) surfaces 36 , the resulting atomic H can then diffuse to other nearby favorable binding sites. However, one caveat is the lower density of sites with negative E H binding , which may prevent the disordered surface from attaining a high H coverage (assuming all B surface remain intact during hydrogenation).…”
Section: Resultsmentioning
confidence: 99%
“…Under hydrogenation conditions, it is reasonable to assume that such sites could function as the predominant “scissors” for H 2 cleavage. As exothermic atomic H diffusion is expected to be facile, exemplified by low H diffusion barriers 35 in bulk MgB 2 and on the pristine Mg-terminated (0001) surfaces 36 , the resulting atomic H can then diffuse to other nearby favorable binding sites. However, one caveat is the lower density of sites with negative E H binding , which may prevent the disordered surface from attaining a high H coverage (assuming all B surface remain intact during hydrogenation).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Wood et al [197] showed that mechanical stresses posed by an external confining medium could affect the thermodynamics and kinetics of phase transformations that occur during the de/rehydrogenation of some CMHs; they focused on incorporating more realistic effects in their models which are usually neglected in computations based on ideal conditions. Some unresolved challenges still plague the application of metal borohydrides for H2 storage.…”
Section: Complex Hydridesmentioning
confidence: 99%
“…After its first inclusion on the research outlook of scientists worldwide in 1996, nano-sized hydrides have known a wide expansion, mainly due to several important kinetic and thermodynamic improvements of nanoconfinement over their bulk counterparts [4,8,14,16,18,[21][22][23]27,28,. Over time, nanoconfinement has emerged as a reliable tool for tuning not only thermodynamic and kinetic behavior at nanoscale, but also for altering reaction pathways, lowering or even suppressing side-reactions and sideproducts, while also affording better size control of the particles over several hydrogen release/uptake cycles (Figure 2).…”
Section: Bulk Vs Nanomaterialsmentioning
confidence: 99%
“…Nanoconfinement of active hydride species inside a porous host bears a number of physical and chemical implications [1,7,8,22,25,27,41,[52][53][54][55][56][59][60][61][62].…”
Section: Physical and Chemical Aspects Of Nanoconfinement Effectsmentioning
confidence: 99%
See 1 more Smart Citation